Agressividade e ansiedade induzidas pelo estresse em peixe-zebra: envolvimento da monoamina oxidase, modulação redox e alterações neuroendócrinas - Quadros, Vanessa Andreatta de (2020)
Mental disorders are considered XXI century pandemics that cause various health diseases. About a third of people have problems related to mental health worldwide. Furthermore, several disorders are triggered by exacerbated fear and anxiety induced by stress. Thus, studying how different stressors can influence biochemical and neurobehavioral responses in experimental laboratory models is an important strategy to clarify the primary mechanism involved in mental disorders. In this study, we investigated the influence of stressors in behavioral responses, as well as in the monoamine oxidase activity (MAO), oxidative stress, and neuroendocrine responses of zebrafish (Danio rerio). In the first study, we evaluated whether acute and chronic alarm substance (AS) exposures modulate aggressive behavior (using the mirror-induced aggression (MIA) test) in wild-type, (WT) and leopard (leo) populations, as well as whether alter brain Z-MAO activity. After acute exposure, AS increased aggression, and decreased Z-MAO activity. Chronically, AS reduced aggression, decreased locomotor activity, and did not alter Z-MAO activity. These data suggest that such responses caused by stress depend on duration of stressor, demonstrating a possible involvement of Z-MAO with the aggressiveness induced by acute stress. In the second study, we evaluated the involvement of repeated stress in anxiety-like behavior (using the light/dark and novel tank tests) and parameters related to oxidative stress in two zebrafish populations. Repeated exposure to AS increased anxiety-like behavior in WT and leo in both tests. Moreover, AS increased the catalase (CAT) and glutathione S-transferase (GST) activities, as well as decreased non-protein thiols (NPSH) levels in both populations. Only in leo we verify an increased in lipid peroxidation (TBARS). We suggest that AS chronically triggers anxiogenic responses and changes brain oxidative stress parameters. In the third work, we investigated whether predictable chronic stress (PCS) using two homotypic stressors, chemical (AS) and physical, net chasing (NC), alters the behavioral and neuroendocrine responses. PCS-AS, but not PCS-NC, increases anxiety-like behavior and cortisol levels in zebrafish. Because both stressors acutely elicited aversive responses, PCS-NC might trigger habituation to stress response. In general, we suggest that PCS induces behavioral and neuroendocrine changes depending on the nature of the stressor. These novel findings described here support the use of zebrafish as an attractive model organism to elucidate the mechanisms of stress in mental disorders, such as anxiety and depression in translational neuropsychiatry.